2023
DOI: 10.1097/md.0000000000034470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different medical masks on acoustic and aerodynamic voice assessment during the COVID-19 pandemic

Abstract: The purpose of the study was to investigate the effect of the surgical masks and N95 masks on the acoustic and aerodynamic parameters of voice assessment during the coronavirus disease 2019 pandemic. The challenge of the study was to enable each inexperienced participant to perform a number of acoustic and aerodynamic voice assessment in a qualified and homogeneous manner without and with medical masks, and to minimize the individual differences. There were 32 healthy participants recruited in the study, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although some systematic reviews and further single studies noted for HNR [ 6 , 8 , 17 , 23 , 24 , 25 ], Jitter [ 26 ], Shimmer [ 24 , 26 ], CPPS [ 18 , 21 ], SPL [ 6 , 8 , 18 , 26 ], and AVQI [ 21 ] significantly effects by RPMs, the present evaluation of this meta-analysis did not support these findings using the software Praat for the signal processing of the included acoustic measures. Further studies that were not included in the present meta-analysis (based on different signal processing methods of the acoustic parameters or other mask types) also concluded that for the same acoustic measures for vocally healthy and voice-disordered individuals, no significant differences between wearing a RPM or not [ 27 , 28 , 29 ]. Moreover, it must be taken into account that voice physiology and voice characteristics may differ between different speakers and between single or multiple voice recordings for consistency of sound measurements [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some systematic reviews and further single studies noted for HNR [ 6 , 8 , 17 , 23 , 24 , 25 ], Jitter [ 26 ], Shimmer [ 24 , 26 ], CPPS [ 18 , 21 ], SPL [ 6 , 8 , 18 , 26 ], and AVQI [ 21 ] significantly effects by RPMs, the present evaluation of this meta-analysis did not support these findings using the software Praat for the signal processing of the included acoustic measures. Further studies that were not included in the present meta-analysis (based on different signal processing methods of the acoustic parameters or other mask types) also concluded that for the same acoustic measures for vocally healthy and voice-disordered individuals, no significant differences between wearing a RPM or not [ 27 , 28 , 29 ]. Moreover, it must be taken into account that voice physiology and voice characteristics may differ between different speakers and between single or multiple voice recordings for consistency of sound measurements [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%